THE EFFECT OF DESTINATION ATTRACTIVENESS ON VISITORS SATISFACTION: THE MEDIATING ROLE OF PLACE ATTACHMENT (Survey on Visitors of Ecotourism: Kampung Wisata Kungkuk, Batu-East Java) - Shoimah, Siti; Nimran, Umar; Al Musadieq, Mochammad (FIA UB, 2014)
Abstract This study examines the causal relationship between Destination Attractiveness, Place Attachment and Visitors Satisfaction of Kampung Wisata Kungkuk, Batu-East Java using PLS (Partial Least Square) analysis. Data were collected from 75 respondents by questionnaire. It was found that Destination Attractiveness has a significant influence on Place Attachment, Destination Attractiveness has a significant influence on Visitors Satisfaction, and Place Attachment has a significant influence on Visitors Satisfaction. Similarly there is relationship between Destination Attractiveness, Place Attachment and Visitors Satisfaction. Equally, the higher attractiveness of destination, the higher are attachment and satisfaction levels. These results will provide potential guidelines for Kampung Wisata Kungkuk to attract and create visitors satisfaction. This study also seeks to contribute to conceptual and strategies by understanding the determinants of environmental destination or ecotourism. Â Keywords: Destination Attractiveness; Place Attachment; Satisfaction; Ecotourism; Tourism Village; Batu-East Java.